2015
DOI: 10.1038/bmt.2015.148
|View full text |Cite
|
Sign up to set email alerts
|

Lower dose anti-thymocyte globulin for GvHD prophylaxis results in improved survival after allogeneic stem cell transplantation

Abstract: In vivo T-cell depletion with anti-thymocyte globulin (ATG) can attenuate GvHD but may increase infection and relapse risks. ATG-Fresenius (ATG-F) at a dose of 60 mg/kg was standard GvHD prophylaxis in unrelated donor hematopoietic stem cell transplantation (HSCT) at our institution. We changed to an incremental reduced dose regimen of 35 mg/kg and extended ATG prophylaxis to include older matched-related donor transplants considered to be at higher risk of GvHD. A total of 265 adults with hematological malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 26 publications
4
42
2
Order By: Relevance
“…The current study was limited to AML in CR1 transplanted with HLA-identical donors to reduce bias due to donor type and disease status on transplant outcomes. As reported in other contexts of allo-SCT [14, 16, 17, 2730], we confirm in the present study that the addition of intermediate dose of thymoglobulin (median, 5 mg/kg) significantly reduces, after adjustment to other factors, the risk of developing cGVHD (Cox HR = 0.46, p  = 0.0001). Compared to patients not receiving ATG, those transplanted with ATG, despite having received more frequently PBSC, had a reduction of 2 years of cumulative incidence of the overall cGVHD from 52 to 31% ( p  = 0.00026) and that of extensive cGVHD from 26 to 8% ( p  < 10 −4 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study was limited to AML in CR1 transplanted with HLA-identical donors to reduce bias due to donor type and disease status on transplant outcomes. As reported in other contexts of allo-SCT [14, 16, 17, 2730], we confirm in the present study that the addition of intermediate dose of thymoglobulin (median, 5 mg/kg) significantly reduces, after adjustment to other factors, the risk of developing cGVHD (Cox HR = 0.46, p  = 0.0001). Compared to patients not receiving ATG, those transplanted with ATG, despite having received more frequently PBSC, had a reduction of 2 years of cumulative incidence of the overall cGVHD from 52 to 31% ( p  = 0.00026) and that of extensive cGVHD from 26 to 8% ( p  < 10 −4 ).…”
Section: Discussionsupporting
confidence: 92%
“…Most patients had received a thymoglobulin dose of <6 mg/kg, so we could not analyze the impact of the ATG dose on outcomes. However, these results are in line with preserved GVL effect despite the addition of low or intermediate doses of ATG in the context of allo-SCT for AML performed with MRD and MUD following conventional MAC [31, 32] and RIC [29, 30, 33, 34], in contrast with increased risk of relapse with doses of thymoglobulin >10 mg/kg [28]. …”
Section: Discussionmentioning
confidence: 81%
“…A number of phase II studies have assessed the impact of rabbit ATG in patients given unmodified grafts after myeloablative conditioning [46][47][48][49][50][51][52] (Table 2). Collectively, these studies suggested that ATG decreased the incidence of grade III-IV acute and chronic GVHD without increasing non-relapse mortality (some studies even found lower non-relapse mortality with ATG), increased the incidence of post-transplantation lymphoproliferative disorders, and improved quality of life.…”
Section: Non-randomized Studies Comparing Anti-thymocyte Globulin Vermentioning
confidence: 99%
“…Secondary end points were acute GvHD (aGvHD) and chronic GvHD (cGvHD), relapse incidence (RI), non-relapse mortality (NRM), GvHD-free, relapse-free survival (GRFS) 20,21 and overall survival (OS). Refined GRFS was defined as survival without the following events: grade 3-4 acute GvHD, severe cGvHD, disease relapse, or death from any cause after Haplo-SCT.…”
Section: Definitions and Statistical Analysismentioning
confidence: 99%